Pelatihan Teknik Mindmap untuk Pengembangan Pembelajaran bagi Pendidik dan Kependidikan Bidang TIK Kabupaten Semarang - Mardi Siswo Utomo; Hari Murti; Widiyanto Tri Handoko; Edy Supriyanto; R. Soelistijadi (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
This community service project addresses the issue of teaching Information and Communication Technology (ICT) in Semarang Regency, which is still dominated by linear methods and lacks visualization, hindering students' comprehension of complex ICT concepts. The goal is to enhance educators' ability to design visual-based teaching modules supported by Dual Coding Theory and Constructivism. The solution provided was an intensive workshop and collaborative mentoring on both manual and digital mind mapping techniques. The results showed a significant increase in educators' cognitive competency, indicated by the average score rising from 55.4% on the pre-test to 88.2% on the post-test. Participants successfully designed digital mind map-based ICT modules with an average product quality score of 88.9%. This success proves the effectiveness of mind mapping as a pedagogical tool for transforming ICT learning into a more active, visual, and structured experience.